2022
DOI: 10.1186/s12913-022-07715-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of introducing multidisciplinary care assessments on access to rheumatology care in British Columbia: an interrupted time series analysis

Abstract: Background In 2011 the British Columbia (BC) Ministry of Health introduced a new fee-for-service billing code that allowed “Multidisciplinary Care Assessment” (MCA). This change has the potential to change access to and quality of care for patients. This study aimed to explore the impact on access to rheumatology services in the province. Methods Fee-for-service rheumatology billings were evaluated for each rheumatologist 2 years before and after u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 54 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…Use of the MCA billing code by a rheumatologist was independently associated with considerably shorter total lag times of 26 days (compared with people seeing rheumatologists who did not bill for this code) and appeared to explain much of the improvement over time. Use of the MCA code has been shown to increase access to rheumatology services, measured as the number of patients seen within a period or the number of services provided 11,17 . Our finding of a shorter lag time associated with the use of this MCA code supports the evidence describing its contribution to improved access to rheumatology services in BC.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Use of the MCA billing code by a rheumatologist was independently associated with considerably shorter total lag times of 26 days (compared with people seeing rheumatologists who did not bill for this code) and appeared to explain much of the improvement over time. Use of the MCA code has been shown to increase access to rheumatology services, measured as the number of patients seen within a period or the number of services provided 11,17 . Our finding of a shorter lag time associated with the use of this MCA code supports the evidence describing its contribution to improved access to rheumatology services in BC.…”
Section: Discussionsupporting
confidence: 76%
“…4,9,10 Previous research showed that use of the MCA code by rheumatologists was associated with an increase in patients seen and services provided by rheumatologists, which was maintained over time. 11 However, it is unknown whether introduction of the code impacted the pathway into rheumatology services for people with symptoms of IA and their ability to receive treatment within the window of opportunity for early treatment. Furthermore, the impact of the expansion of the number of rheumatologists on the referral process has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that the introduction of the MCA code did not change the number of unique patients seen by rheumatologists; however, we observed a reduction in the number of days between visits for patients with RA whose rheumatologists used the MCA code. Past research found that the introduction of the code was associated with increased numbers of patients seen 2,6 and services provided. 6 Beyond access, evidence suggests that the MCA may change the nature of clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…2 This includes increasing the overall volume of patients seen, the number of services provided by rheumatologists, and reducing wait times for new patients. 2,[4][5][6] One remaining question regarding the MCA code is its impact on health system costs. More than 70% of BC rheumatologists now use the MCA code, billing it 30,000 times in 2022 at a total cost of $6.5 million.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatology is mainly an outpatient specialty, with patients' clinical visits often comprising a major aspect of care (1). Timely initiation and sustained maintenance of medical interventions, which typically occur at clinical visits, are associated with improved prognosis and symptomatic amelioration in many rheumatic diseases (2). However, the appropriate frequency to visit a physician for rheumatic disease follow-up has not been a major focus of study (3), resulting in a lack of guidance for rheumatic disease follow-up for common conditions like rheumatoid arthritis (RA) (4) and osteoarthritis (OA) (5).…”
Section: Introductionmentioning
confidence: 99%